Davvero le diseguaglianze sono un male? Due teorie che non funzionano - Pellegrino, Gianfranco (Filosofia Morale/Moral Philosophy, 2023)
The paper deals with the disvalue of inequality. After distinguishing the view that inequality is instrumentally bad from the view that it is non-instrumentally bad, the paper considers two ways to ground the disvalue of inequality. According to some authors, inequality is bad as it constitutes unfairness. Others suggest that inequality is bad because it is morally arbitrary. The paper suggests that both views have problems. It seems that the ground of the non-instrumental disvalue of inequality is still to be found.